LIS input to degree programmes offered at the Faculty of Computer Science and Information Technology, University of Malaya - Abrizah, Abdullah; Zainab, Awang Ngah; Edzan, N.N.; Khaizura, M.K. (2001)
The Faculty of Computer Science and Information Technology (FCSIT) at the University of Malaya was established in 1994 and currently offers two main undergraduate degree programmes (Bachelor of Computer Science [BCS] and Bachelor of Information Technology) and four Master programmes (Master of Computer Science, Master of Software Engineering, Master of Information Technology and Master of Library and Information Science [MLIS]). Each degree programmes provide opportunities for specialisation. The Bachelor in Computer Science offers specialisation in Computer Systems and Networks, Management Information Systems, Software Engineering and Artificial Intelligence. The Bachelor of Information Technology (BIT) provides special modules biased towards IT applications in Financial Management, Multimedia and Information Science This paper focuses on LIS input to the BIT (Information Science) and MLIS degree programmes offered at FCSIT. Five academic staffs are responsible for planning and teaching the LIS components in these two programmes. The BIT (IS) degree is a three year programme, that aims to expose information technologists to the types and characteristics of information sources and services and understand the behaviour of information users. This would enable these IT professionals develop and manage meaningful and usable information systems, product and services. Hence, the BIT (IS) graduates could function in organisations that manages knowledge or information portals and systems. The MLIS programme offered at the Faculty is about 6 years old and its curriculum have been revised in the year 2000 to cater for current needs of information professionals. The present programme tries to provide a balance between LIS contents and a working knowledge of planning and managing information systems. Thus, the core courses offered stay close to basic LIS information subjects (information sources, services management, organisation, storage, retrieval and IT applications). The difference can be seen in the elective courses where more IT related courses are offered (Information systems development, multimedia systems, basic visual programming, knowledge management, electronic publishing, digital libraries, Internet resource management, and human factors in information systems). For balance more traditional LIS electives are maintained (Collection development, Information sources in specific fields, individual study, and library practicum). On the whole FCSIT have also emphasized on research and the development of useful systems. Each undergraduate are required to produce a research report and develop a fully running systems as part of the requirement for the degree that comprises nine credit hours. In this respect, LIS academic staff have taken advantage of this situation by encouraging undergraduates (BCS and BIT) to development LIS related projects that ranged from library automated systems for small libraries, graphical based library systems for children, bar-coding generating system, knowledge portals, adviser systems, digital library hosting systems and content databases. There is an urgent need for collaboration between faculty and libraries, information centres, as well publishers in ensuring the systems developed are knowledge or content rich. This collaboration places LIS professionals as an active partner and content provider for information-rich local-content knowledge systems. A brief description of LIS systems that have been developed is appended.